Porous catalyst support from clay-precipitated calcium carbonate for carbon nanomaterials growth - Yasmin Yuriz (School of Materials Engineering, 2016)
The present study is mainly to develop a catalyst support for CNMs growth. The primary objectives of this project are divided into the following categories, to fabricate a catalyst support from clay and controlled amounts of PCC via a polymeric foam replication method. To analyse the physical and mechanical properties of the catalyst support at various amounts of PCC and different milling durations. To investigate the correlation of mechanical strength over the percentage of porosity and foam density of the catalyst support via statistical analysis. To evaluate the feasibility of the growth of CNMs on the porous ceramic.